Cervical Vagal Swannoma: A Case Report (Bangladesh Journal of Otorhinolaryngology, 2016)
Cervical vagal schwannomas are rare, slow growing tumours usually occur in patients between thirty and fifty years of age with no sex related predisposition. They are usually asymptomatic benign lesion and complete surgical resection with preservation of neural pathway, whenever possible is the treatment of choice.Bangladesh J Otorhinolaryngol; October 2015; 21(2): 115-118